2014
DOI: 10.4028/www.scientific.net/amm.699.15
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Curing Conditions on the Mechanical Properties of Fly Ash-Based Geopolymer without Sodium Silicate Solution

Abstract: Geopolymer is associated with the alkali activation of materials rich in Si and Al, and alkali activator such as sodium hydroxide is used for the dissolution of raw material with the addition of sodium silicate solution to increase the dissolution process. However, the trend of strength development of geopolymer using sodium hydroxide alone is not well established. This paper presents an evaluation on compressive strength of fly ash–based geopolymer by varying curing time with respect to different curing tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
0
0
Order By: Relevance
“…Based on Figure 2, the compressive strength increased up to 14 days but started to decrease later for all solid/liquid ratios. The similar trend was reported in previous study [9]. It has been reported that prolong curing time at elevated temperature can damage the structure of geopolymer and lead to the decrease of compressive strength [10].…”
Section: B Effect Of Solid/liquid Ratio and Curing Time On The Compre...supporting
confidence: 90%
See 2 more Smart Citations
“…Based on Figure 2, the compressive strength increased up to 14 days but started to decrease later for all solid/liquid ratios. The similar trend was reported in previous study [9]. It has been reported that prolong curing time at elevated temperature can damage the structure of geopolymer and lead to the decrease of compressive strength [10].…”
Section: B Effect Of Solid/liquid Ratio and Curing Time On The Compre...supporting
confidence: 90%
“…Based on Figure 1, the increase of solid/liquid ratio used results in reduction of setting time. This can be associated to the less of water available as the solid/liquid ratio increased and result in faster hardening of gel phase and more rapidly bonding of the geopolymeric framework [9].…”
Section: A Effect Of Solid/liquid Ratio On the Setting Timementioning
confidence: 99%
See 1 more Smart Citation
“…The supply of heat seems to accelerate geopolymerisation process until it reaches optimum strength at 14 days. However, prolong curing time after 14 days in elevated temperature result in destruction of geopolymer bonding and produced lower compressive strength [10].…”
Section: Effect Of Different Alkali Activatormentioning
confidence: 99%